The ring in the rubble : - Bradt, Gary (McGraw-Hill, 2007)
Gary Bradt is a prominent authority on leadership and change and a close colleague of Spencer Johnson, author of Who Moved My Cheese?. In The Ring in the Rubble, Bradt presents the intriguing metaphor of a golden ring buried beneath the rubble of sudden change and offers 10 guideposts for navigating uncertainty, recognizing this ring of opportunity, and seizing hold of it at the right time. He also asks revealing questions that help readers “dig a little deeper”-understanding the nature of this opportunity, using it to their best advantage and finding lasting success in an ever-changing world.